A parametric definition for a family of inheritance reasoners - VOGEL, CARL (Springer Verlag, 1997)
This paper gives a declarative specication of a popular inheritance system and shows how simple changes to this specication can result in dierent pathbased reasoners This parameterized denition provides a deeper understanding of the fundamental dierences between some of the more popular pathbased inheritance reasoners In particular it allows the clarication of some of the results on the complexity of reasoning in the various systems The uniform framework also allows definition of novel systems which constitute intermediate points in the space of possible reasoners and facilitates perspicuous Prolog implementation
PUBLISHED
Keywords: Computer Science